Influence of supply chain integration, Islamic human capital and halal supply chain integrity on Halal herbal-based food SMEs' performance - Rajendran, Salini Devi (2020)
Both Muslims and non-Muslims perceive halal herbal-based food products to be clean hygiene, and nutritious. Although halal certification and logo provide a promising assurance that the whole supply chain complies with the Shariah law, however, several unethical cases have affected the herbal-based food products. The supply chain activities possess a high potential to influence halal integrity along the herbal-based food products supply chain. All players in the herbal-based food products supply chain should take responsibility to preserve integrity as it cannot be guaranteed if the other players do not practice similar halal practices. In the halal business, the business owner or manager should be equipped with the technical knowledge, skills, and experience based on the Islamic view to manage and execute the halal business and services. Hence, the objective of this study is to investigate the influence of the supply chain integration (SCI) and Islamic human capital practices on the halal supply chain integrity (HSCI), and its influence on herbal-based food SMEs' performance. Three prominent theories, namely Strategy-Structure-Performance (SSP), Resource-Based View (RBV), and Human Capital Theory were employed to describe the variables. Seven hypotheses were proposed to determine the relationship between the supply chain integration (SCI) Islamic human capital, halal supply chain integrity (HSCI), and herbal-based food SMEs' performance. A quantitative meth0dology was applied, and data were collected using an interviewer-administered questionnaire. The convenience sampling technique was employed to choose 176 halal herbal-based food SMEs located in Peninsular Malaysia. Both SPSS and Partial Least Squares-Structural Equation Modelling (PLS SEM) were used for data analysis. The key finding revealed that both the SCI and Islamic human capital positively influenced the HSCI. Moreover, the HSCI has also positively influenced the herbal-based food SMEs' perfonnance. Further analysis also supported the mediating effect of HSCI in influencing herbal-based food SMEs' perfonnance. Practically, the inputs gained from this research could potentially be beneficial to various stakeholders, specifically academics, practitioners, (halal manufacturers, business owners, or managers) and policymakers. Based on the theoretical implications, this study has specifically extended several theories such as the Strategy-Structure-Performance (SSP), Resource-Based View (RBV), and Human Capital Theory into the halal product management and halal supply chain integrity (HSCI) within the field of halal supply chain management. Furthermore, the study has provided implications for the halal herbal-based food SMEs in terms of prioritizing on cross-functional integration within the firms and further improvement on the Islamic human capital development with halal supply chain knowledge and religious orientation. Lastly, this study contributed to policymakers that herbal-based food production should be focused on the aspects of halal product management with the application of Islamic principles.